(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
This article examines the possibility of invoking the protection of legitimateexpectations under the fair and equitable treatment standard to strike downquestionable regulatory changes taken by a host State in investor-State investmentarbitrations. Drawing from jurisprudence of investment arbitral tribunals,it also lays out two tests that regulatory changes have to withstand in order to be legitimate under the fair and equitable treatment. Finally, it engages in preliminaryinvestigations into the general justifications available for host States to justifythe regulatory changes, in case these measures are potentially or establishedas violations to the fair and equitable treatment.